Efektifitas Dosis Minyak Pala Untuk Pemingsanan Ikan Nila (Oreochromis niloticus) Selama Transportasi - Khalil, Munawwar; Yuskarina, Yuskarina; Hartami, Prama (Agrium, 2013)
This research was done on 08th – 10th August, 2011 at Countryside of Alue Keurinyai Banda Baro District, North Aceh Sub-province, Aceh Province. The aim of this research was to know doze effectivity of pala oil for tilapia (oreochromis niloticus) fainting while transportation. This research used non factorial completely randomized treatment with three replications on each treatments that using 0,8; 0,9; 1 and 1,1 ppm doze. The test observed in this research was the speed of fainting fish, insensible recovery, and survival rate on each treatments. Result showed us that the fourth experiment was the speedest faint, while the first experiment was the speedest insensible recovery. While in survival rate, the first experiment was showed the best result, where the percentage value reachs 58,33%. Based on statistical analyze showed that f count > f table in 99.99 % level of trust for all tested observe.